Temperature response of luminescent tris(bipyridine)ruthenium(II)-doped silica nanoparticles - Mirenda, Martin (2013)
Nanoparticle-based temperature imaging is an emerging field of advanced applications. Herein, the sensitivity of the phosphorescence of tris(bipyridine)ruthenium(II)-doped silica nanoparticles towards temperature is studied. 130 nm size particles were prepared by a modification of Stöber’s method, that allows the incorporation of Ru[(bpy)3]2+ into the outer particle shell. The entrapped Ru[(bpy)3]2+ retains its photophysical properties, yet the emission of the particles is not affected by the presence of O2, neither by anionic quenchers; quenching by MV2+, on the other hand, is strongly dependent on pH. Between 20 and 60 °C, the steady-state emission of the particles decreases linearly with increasing temperature. The slope of the straight line diminishes slightly on thermal cycling, but soon stabilizes. Fluorescence measurements by scanning confocal microscopy indicate that the silica nanoparticles doped with Ru[(bpy)3]2+ can indeed be employed to probe thermal processes in micro-environments.